Towards A Comprehensive Framework For Technology Selection And Capacity Planning For Sustainable Manufacturing - Nejadi, Fahimeh; Cheng, Kai (European Scientific Journal, ESJ, 2016)
Technology mixed perspective, as a combination of two functions of ‘Technology Selection’ and ‘Capacity Planning’, is not usually addressed in the research literature. Yet, the importance of integrated decisions at such strategic level is evident. The overall aim of this paper is to develop a framework for combined ‘technology selection’ and ‘capacity planning’ in manufacturing sector. The approach will also incorporate the multiperspective concept of sustainability, while taking uncertainties into account.